Safety, tolerability, and pharmacokinetics of fluoropezil (DC20), a novel acetylcholinesterase inhibitor: A phase I study in healthy young and elderly Chinese subjects - Hongjie Qian; Chengyin Yu; Huijuan Zhu; Qichen Ding; Yuting Cai; Jiao Jing; Xin Xu; Runcong Guo; Haiyan Zhang; Hong Liu; Xiaoyan Chen; Yun Liu (Wiley, 2023)
Abstract The present study evaluated the safety, tolerability, and pharmacokinetics of fluoropezil (DC20), a novel acetylcholinesterase inhibitor under development for the treatment of Alzheimer's disease (AD) in otherwise healthy young and elderly Chinese subjects. The study of young subjects included the multiple ascending dose (MAD) arm (2 and 6 mg, N = 24) and the food effect arm (4 mg, N = 12) and was followed by the study of elderly subjects who were given (2 and 4 mg, N = 11). The noncompartmental analysis method was used to determine the pharmacokinetic parameters. The pharmacokinetics of fed versus fasted dose administration in the same subjects was assessed by 90% confidence interval. In the MAD arm, the accumulation ratios of DC20 in vivo were 2.29 and 2.15, respectively. In the food effect arm, compared with fasting administration, an area under the concentration‐time curve from zero to t after a standard and high‐fat diet orally administered slightly increased by about 19% and 29%, and the time to maximum concentration (Tmax) was delayed by around 1 h. For elderly study subjects, Tmax was 1.5 and 1.25 h, and terminal half‐life (t1/2) was 77.1 and 74.2 h, respectively. There were no serious adverse events (AEs), whereas gastrointestinal reactions were the most common AEs associated with the study drug. We predicted the safety risks of DC20 in the clinical treatment of AD, which were well‐tolerated by the healthy young and elderly subjects. The elimination of DC20 from the body was slower in elderly subjects than in young subjects. This study was approved by the Center for Drug Evaluation, National Medical Products Administration (CTR20181428, CTR20190664, CTR20191878, and CTR20192724).